2016
DOI: 10.1186/s40634-016-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell concentration correlates with increased concentrations of IL-1ra and improvement in WOMAC pain scores in an open-label safety study of autologous protein solution

Abstract: BackgroundThere has been debate on which blood components should be included in autologous therapies. Autologous Protein Solution (APS) is a unique blood-derived therapy composed of concentrated white blood cells, platelets, and plasma to contain high concentrations of anti-inflammatory cytokines and anabolic growth factors to potentially address osteoarthritis. The primary aim of the exploratory secondary analysis was to identify characteristics of an Autologous Protein Solution (APS) that may correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…37 Alternatively, there has not been any correlation between the concentration of WBCs in APS and inflammatory cytokines. 17 In this meniscal-tear study with APS, no adverse events were reported. Gait analysis (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…37 Alternatively, there has not been any correlation between the concentration of WBCs in APS and inflammatory cytokines. 17 In this meniscal-tear study with APS, no adverse events were reported. Gait analysis (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Subjects with IL-1ra:IL-1b ratios greater than 1000 or with high WBC concentrations in their APS were more likely to be Outcome Measures in Rheumatology-Osteoarthritis Research Society International (OMERACT-OARSI) high pain responders. [17][18][19] These results support the use of APS as a method of directly interfering with the inflammatory molecular pathways causing OA, reducing pain and improving function simultaneously.…”
mentioning
confidence: 63%
See 3 more Smart Citations